(untitled) (Mustansiria Dental Journal, 2019)
Background: Fixed orthodontic appliance considered a risk factor that effect oral health status. Aims of this study were evaluation of oral hygiene, gingival health and caries experience among patients with fixed orthodontic appliance at different time intervals of treatment. Material & Methods:- 32 patients (24 female and 8 male) included in this study and they underwent clinical examination plaque, calculus, gingival health and caries experience by using Loe, 1967, Green and vermillion, 1960 and WHO, 1987 indices at four time intervals: 2-3 weeks after appliance insertion, 2 months, 4 months, 6 months. The statistical analysis of data was by using statistical Package for social Sciences (SPSS version 18). Results:- The means of all variables examined increased during six months of orthodontic treatment with high significant difference during visits. 49.6% of patients developed new caries lesions after six months of treatment. Conclusion:- Patients underwent orthodontic treatment at high risk for developing oral health problems.